Aeolian sand transport thresholds in excavated foredune notches. Issue 2 (1st November 2021) - Nguyen, Duc; Hilton, Michael; Wakes, Sarah
Abstract: Excavation of 'notches' in foredunes aims to facilitate sand transport through the foredune zone to enhance biodiversity and increase foredune resilience. Recent research has examined notch morphodynamics, however, the underlying aeolian processes in relation to sand transport have not been examined. This study determines: (i) the critical incident wind conditions resulting in sand transport inside the notch; and (ii) the pattern of wind flow and sand deposition/erosion inside the notch. Secondary winds are recorded using 12 ultrasonic anemometers deployed at cross‐notch stations and compared with incident winds measured on a mast 6.5 m above foredune crest. Instantaneous sand transport is recorded using 12 laser particle counters located on four masts across the notch. Sand deposition is measured using erosion pins and digital surface models derived from remotely piloted aerial system. Field data are used to validate Computational Fluid Dynamic wind flow simulations to provide three‐dimensional wind direction and speed contours in the notch. The study area is St Kilda Beach, Dunedin, New Zealand. Sand transport occurs inside the notch when incident wind speed and approach angle are 15 ms −1, 17 ms −1 and 23 ms −1 and 40°, 48° and 55°, respectively, to the notch orientation. When the incident wind speed and direction is 15 ms −1 and 40°, respectively, wind speed inside the notch at the western side (upwind) (6.2 ms −1 ) is lower than at the eastern side (8 ms −1 ), resulting in deposition on the western side and erosion on the eastern side. The near‐surface wind directions are at an angle (14°) to notch orientation toward the northwest and result in deposition on the western side of the depositional lobe downwind of the notch. These results assist dune managers to determine the appropriate notch angle to the prevailing wind direction, to maximise sand transport through the notch in a wide range of conditions. Abstract : During incident oblique winds (>60° relative to the shore perpendicular), alongshore sand transport on the beach might be steered into the excavated foredune notches.